Indications for the measurement of plasma digoxin concentrations. - Aronson, J (1983)
The criteria which a drug must fulfil before it can be said that it may be worthwhile making regular plasma concentration measurements of that drug in monitoring therapy are described in this article. In particular, these criteria are discussed in relation to digoxin. The criteria completely fulfilled by digoxin are that it has a low toxic: therapeutic ratio, that there is a poor relationship between dose and plasma digoxin concentration, that the signs and symptoms of digitalis toxicity may be difficult to distinguish from those of the disease, and that the therapeutic effects may sometimes be difficult to measure. The criterion partly fulfilled by digoxin is that it should not have active metabolites which contribute to the therapeutic/toxic effects of the drug but which cannot be reliably measured with ease. Although in most patients digoxin is poorly metabolised, in about 10 to 15% it may be extensively metabolised to active compounds. Certain factors affect one's interpretation of the plasma digoxin concentration. They can be considered in 2 groups: (a) those factors which change the plasma digoxin concentration resulting from a constant dose of digoxin; and (b) those factors which cause a change in the pharmacodynamic or therapeutic response resulting from a constant plasma digoxin concentration. The most important factors in the first category are renal impairment and drug interactions (particularly the interaction of digoxin with quinidine), although even in these circumstances the concentration/effect relationship may also be disturbed. The most important factors in the second category are disturbances of electrolyte balance (particularly hypokalaemia) and abnormalities of thyroid function. For this reason, the plasma potassium concentration should be measured every time the plasma digoxin concentration is measured. Measurement of the plasma digoxin concentration may be of value when tailoring the digoxin dosage to individual requirements, in the diagnosis of digoxin toxicity, in determining the need for long term therapy, and in diagnosing digoxin overdosage. In tailoring the dose of digoxin to individual requirements, plasma digoxin concentration measurement is most useful if the patient's previous drug history is uncertain, if there is a poor response to treatment, when there is changing renal function, or when an interacting drug is introduced (particularly quinidine). In aiding the diagnosis of digoxin toxicity, a plasma digoxin concentration greater than 3 ng/ml suggests toxicity, but plasma digoxin concentrations below 3 ng/ml may or may not be associated with toxicity. Consideration of other factors (such as plasma potassium concentration, renal function, age, daily dose) may help to refine one's use of the plasma digoxin concentration but in each individual case, careful clinical assessment may be a major factor in diagnosing digitalis toxicity. Patients who have been taking digoxin for more than a few weeks, whose clinical condition is stable, and whose plasma digoxin concentration is below 0.8 ng/ml do not usually require long term digoxin treatment and withdrawal of digoxin in such cases is usually not followed by clinical deterioration. In digoxin overdosage, plasma digoxin concentration measurement serves to confirm the extent of overdosage but the plasma potassium concentration gives a better guide to prognosis.